Translating Singaporean folktales and legends for moral education : a case study of selected short stories from Asian favourite stories - Lim, Jing Xian (2019)
Character and Citizenship Education (CCE) is an important component of the Singapore education system. In conducting CCE lessons during Mother Tongue lessons, teachers use a variety of resources as aids, one of which is the use of stories. Presently, the CCE textbook lacks Singapore stories featuring folktales and legends. Through the use of suitable translation theories and strategies, six local stories have been translated from the English to Chinese language and incorporated in this study which aims to discuss the advantages of using such translated material as a CCE teaching resource, facilitating teachers in conducting lessons designed to develop students into citizens with knowledge of “National and Cultural Identity (LO5)” and “Socio-Cultural Sensitivity and Awareness (LO6)”. A total of ten participants from a local primary school volunteered to take part in this study. The participants were given the translated stories to read with a questionnaire to complete after reading. The responses were analysed and presented in the form of pie charts. The study revealed findings about the advantages of using the translated local stories, the teaching points of each story, the use of annotations as well as some foreseeable issues in using the selected stories as a teaching resource. As a whole, the study demonstrated that there is value in using translated local stories to conduct CCE lessons.